Segregative cell division and the cytoskeleton in two species of the genus Struvea (Cladophorales, Ulvophyceae, Chlorophyta). Issue 4 (25th August 2016) - Okuda, Kazuo; Sekida, Satoko; Hasebe, Ami; Iwabuchi, Misa; Kamiya, Mitsunobu; Hishinuma, Tasuku
SUMMARY: The detailed segregative cell division (SCD) processes and changes in the arrangement of cortical microtubules and actin filaments were examined in two species of Struvea . SCD was initiated by the appearance of annular constrictions along the lateral side of a mother cell. The constrictions decreased in diameter, became thin, tubular in shape, and pinched the protoplasm of the mother cell into several protoplasmic sections. The protoplasmic sections expanded and developed into daughter cells, which appressed each other, and were arranged in a single row. Lateral branches protruded from the upper parts of the daughter cells. The protoplasm of the lateral branches was divided by secondary SCDs and was distributed amongst the new daughter cells. SCD and lateral branch formation were essential for morphogenesis in Struvea . Cortical microtubules were arranged parallel and longitudinally to the cell axis before SCD. When SCD was initiated, there was considerable undulation of the cortical microtubules and several transverse bundles appeared in the cytoplasmic zone where annular constrictions occurred. A microtubule‐disrupting drug (amiprophos methyl) inhibited SCD. Actin filaments maintained reticulate patterns before and during SCD. These results demonstrated that SCD in Struvea species was quite distinct from that in Dictyosphaeria cavernosa reported previously.